Diversity Challenge in Skin Care: Adaptations of a Simple Emulsion for Efficient Moisturization across Multiple Geographies - Alicia Roso; Catherine Kern; Sophie Cambos; Christine Garcia (Applied Sciences, 2023)
Moisturization is a primary need in skin care. This study aimed to investigate whether the C12-C20 glucolipid emulsifier could provide minimalist water-in-oil emulsions (i.e., a minimum number of ingredients, in reasonable quantities) with a significant moisturizing effect across multiple geographies even if the emulsion structure needed to be adapted to meet local expectations. Four structures were tested containing a stabilizer and an oily phase that were adapted to address consumers’ skin feel expectations in each location. In vivo corneometry and transepidermal water loss (TEWL) measurements were carried out on volunteers with dry skin up to 24 h after application (leg or forearm; phototypes I to VI). The first investigation was completed in France comparing corneometry measurements to the control without the emulsifier and an untreated area. Studies were then performed in Brazil, India and Mauritius, combining corneometry and TEWL assessments. Significant increase in skin capacitance was observed in the four countries, compared to the untreated area, at 5/6/8 h after application and up to 24 h. The effect was also significant versus the control in the French study at 5 h. A significant decrease in TEWL compared to the untreated area was observed concurrently in Brazil, India and Mauritius.